2020
DOI: 10.1016/j.psychres.2019.112624
|View full text |Cite
|
Sign up to set email alerts
|

Towards the objective assessment of suicidal states: Some neurocognitive deficits may be temporally related to suicide attempt

Abstract: Neurocognitive detection of suicidal states has the potential to significantly advance objective risk assessment. This goal requires establishing that neurocognitive deficits fluctuate around the time of a suicide attempt. The current study therefore evaluated whether neurocognitive performance is temporally related to suicide attempt, in a sample at high-risk for suicide (n=141). Evaluations consisted of a clinician-administered interview, self-report questionnaires, and neurocognitive tasks assessing respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…Previous studies that have examined the temporal associations between cognition and SITs were mismatched in their respective time scales (Cha et al, 2010;Interian et al, 2019) in that the measure of SITs could cover an epoch of weeks to years, whereas the measure of cognition might reflect cognitive resources in that moment. This study improves on the temporal precision of these prior retrospective studies by matching measures in time scale.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have examined the temporal associations between cognition and SITs were mismatched in their respective time scales (Cha et al, 2010;Interian et al, 2019) in that the measure of SITs could cover an epoch of weeks to years, whereas the measure of cognition might reflect cognitive resources in that moment. This study improves on the temporal precision of these prior retrospective studies by matching measures in time scale.…”
Section: Discussionmentioning
confidence: 99%
“…The attentional bias to the suicide-related words may be detectable only among recent suicide attempters, but there were few participants in the present sample ( N = 9, 17.3%) that had a history of suicide attempt within 1 week of enrollment in the study (see Table 1 ). Participants who made attempts more than 1 week prior may be less sensitive to suicide related stimuli ( 41 ) with RT related to the proximity of the last attempt ( 12 ). Attentional bias for suicide-related words was associated only with suicide attempt occurred within the past week in studies taking place in the emergency room ( 10 ) or in inpatient units where patients had been admitted for acute clinical care ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found that depressed attempters were clearly distinguished by a deficit in response inhibition (Go/No-go commission errors) [29]. A recent study found that the neurocognitive assessment of response inhibition and memory recognition shows sensitivity to the recency of a SA which suggested that phasic neurocognitive deficits may serve as objective markers of short-term suicide risk [30].…”
Section: Response Inhibitionmentioning
confidence: 97%